China's industrial decarbonization in the context of carbon neutrality: A sub-sectoral analysis based on integrated modelling. (December 2022) - Shao, Tianming; Pan, Xunzhang; Li, Xiang; Zhou, Sheng; Zhang, Shu; Chen, Wenying
Abstract: China's 2060 carbon neutrality requires the industrial sector to play a leading role in decarbonization. By refining China's industrial sector into 11 specific subsectors in the Global Change Analysis Model and representing industrial carbon capture and storage (CCS) and hydrogen, this study conducts a sub-sectoral analysis of China's industrial decarbonization under three carbon neutrality scenarios and explores the potential role of CCS and hydrogen. Regardless of the scenario, the results show that China's industrial CO2 emissions peak during the 14th Five-Year Plan period, with a reduction of about 90% in 2050 compared to 2020; electricity becomes the primary energy for China's industrial sector by around 2035, with industrial electrification reaching about 64% in 2050, while coal and oil change from fuel to feedstock. Tapping the mitigation potential of cement, steel, and chemical is a fundamental requirement for China's industrial decarbonization, while further deeper mitigation requires more additional efforts in other subsectors. Cement, steel, and chemical need to reach peak CO2 by the 14th Five-Year Plan period, and together they are responsible for 83–85% of total industrial emissions reductions from 2015 to 2050. An important way to reduce emissions from these three subsectors is to reduce energy consumption. The other industrial subsectors are expected to reach peak CO2 by the 15th Five-Year Plan period. Increasing the electrification rate is a key way to reduce emissions in other subsectors. CCS and hydrogen can play an important role in decarbonizing China's industrial sector. In the scenarios of this study, the annual deployment of CCS in China's industrial energy use exceeds 0.3 GtCO2 in 2035–2040, while hydrogen provides 5.2–10.4% of total industrial energy use in 2050. Graphical abstract: Image 1 Highlights: China's sub-sectoral industrial decarbonization is assessed under carbon neutrality. China's 2050 industrial CO2 reduces to about 90% below 2020 levels. Tapping mitigation potential of cement, steel and chemical is a basic requirement. Electricity becomes the primary industrial energy by around 2035. Carbon capture and storage and hydrogen can play an important role.